2015
DOI: 10.1016/j.neures.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Histological and electrophysiological analysis of the corticospinal pathway to forelimb motoneurons in common marmosets

Abstract: Using histological and electrophysiological methods, we identified the neuroanatomical properties of the common marmoset corticospinal tract (CST), which underlies hand/arm motor control. Biotinylated dextran amine (BDA) was injected into the primary motor cortex to anterogradely label CST axons in the cervical segments, revealing that most CST axons descend in the contralateral dorsolateral funiculus (DLF; 85.0%), and some in the ipsilateral DLF (10.7%). Terminal buttons were mainly found in the contralateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…Findings in rhesus monkeys were replicated in marmoset monkeys where 11% of M1 CST fibers descended ipsilaterally through the dorsolateral funiculus and terminated in laminae VII–VIII [42]. These studies suggest that ipsilateral M1 may partake in the control of proximal and potentially distal muscles.…”
Section: Icst In Non-human Primatesmentioning
confidence: 90%
See 1 more Smart Citation
“…Findings in rhesus monkeys were replicated in marmoset monkeys where 11% of M1 CST fibers descended ipsilaterally through the dorsolateral funiculus and terminated in laminae VII–VIII [42]. These studies suggest that ipsilateral M1 may partake in the control of proximal and potentially distal muscles.…”
Section: Icst In Non-human Primatesmentioning
confidence: 90%
“…However, a significant ipsilateral response was predominantly recorded in proximal or truncal muscles upon stimulation of SMA [44, 45], and, occasionally, M1 [43]. In vivo cortical stimulation studies performed in rhesus [24] and marmoset monkeys [42] showed that ipsilateral M1 projections are not monosynaptic. Although the lack of monosynaptic connection is not unanticipated given that the majority of contralateral fibers also do not monosynaptically connect to motor neurons, the presence of polysynaptic connections does not rule out the involvement of the contralateral hemisphere or contralateral brainstem nuclei upon stimulation of ipsilateral cortical regions.…”
Section: Icst In Non-human Primatesmentioning
confidence: 99%
“…), and it is generally thought that they lack direct cortico‐motoneuronal projections to distal hand muscles (Lemon & Griffiths, ; Kondo et al . ; Walker et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Dark grey cortical fields represent those areas in which cells projecting to M1 were found in any of the cases described by Burman et al, , b. Brachial spinal segments illustrated with motor pools colored according to their corresponding upper limb musculature as described by Watson et al (), see text for details. Inset: Illustration of BDA labeling at C7 after injection in M1 as in Kondo et al (). [Color figure can be viewed at http://wileyonlinelibrary.com]…”
Section: Current and Comparative Understanding Of The Marmoset Motor mentioning
confidence: 99%